In vitro and in vivo comparative performance studies of gadolinium-loaded zeolites and Gd-DOTA as contrast agents for MRI applications - Contro, Janine [UNESP]; Silva, Danilo Antonio [UNESP]; Santisteban, Oscar A. N. [UNESP]; Narayana, Ponnada A.; Nery, José G. [UNESP] (Wiley, 2021)
Gadolinium-based contrast agents (CAs) were synthesized using faujasite zeolite (NaX) and zeolite beta (BEA) and their performances in vitro and in vivo were compared to the widely used commercial CA, gadoteric acid (Gd-DOTA). Magnetic resonance imaging (MRI) relaxometry studies (considering longitudinal [T1] and transverse [T2] relaxation times) were performed using Gd-DOTA and the zeolitic materials loaded with Gd3+. The Gd-loaded NaX, which presented large pores and cavities (7.35 and 11.24 Å, respectively), exhibited relaxivity values of around 52 mM−1 s−1, while BEA, which presented smaller pore and cavity diameters (5.95 and 6.68 Å, respectively) showed lower relaxivity values of ~4.8 mM−1 s−1. The effect of the Gd-loaded NaX as MRI CA was tested in vivo in Sprague–Dawley rats, employing a 7 T scanner, with comparison to Gd-DOTA MRI angiography. The relaxivity measurements showed that the Gd-loaded NaX (50 mM−1 s−1) provided better image contrast than Gd-DOTA (5.1 mM−1 s−1). Clearance studies of the CAs using urine and blood showed that both Gd-loaded NaX and Gd-DOTA were eliminated from the body after 2 days, demonstrating the potential of Gd-loaded NaX for use as an MRI CA.
Keywords: contrast agent; gadolinium; Gd-DOTA; relaxivity; zeolite